2015
DOI: 10.4103/0975-7406.163450
|View full text |Cite
|
Sign up to set email alerts
|

Denture bar-coding: An innovative technique in forensic dentistry

Abstract: Denture markers play an important role in forensic odontology and also in identifying a person. A number of methods are there for identifying dentures from a less expensive technique to a more expensive technique. Out of different denture markers, the bar-coding system is a way of collecting data from the mobile. Even a huge amount of data can be stored in that. It can be easily incorporated during acrylization of the denture and thus could be helpful in identification. This article reviews the strengths of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Studies have revealed that photographic papers/ bar code markers are resistant to a temperature of 200-300 • C. Richmond and Pretty have stated that markers which can be damaged with fire should be positioned palatally or lingually in the maxillary or mandibular molar region so that they can be protectd by the tongue. 8 Micro SD card is an important marking device which can be incorporated in the lingual flange of mandibular prosthesis or buccal flange of maxillary prosthesis. 9 These locations does not pose any esthetic problems and are well protected by buccal mucosa.…”
Section: Discusssionmentioning
confidence: 99%
“…Studies have revealed that photographic papers/ bar code markers are resistant to a temperature of 200-300 • C. Richmond and Pretty have stated that markers which can be damaged with fire should be positioned palatally or lingually in the maxillary or mandibular molar region so that they can be protectd by the tongue. 8 Micro SD card is an important marking device which can be incorporated in the lingual flange of mandibular prosthesis or buccal flange of maxillary prosthesis. 9 These locations does not pose any esthetic problems and are well protected by buccal mucosa.…”
Section: Discusssionmentioning
confidence: 99%
“…El código se localizará en la zona superior a nivel de la superficie palatina y en zona inferior a nivel de la pestaña distolingual. Para terminar, los códigos serán colocados en sus respectivos lugares donde se procederá a cubrirlos con resina acrílica transparentes para luego ser pulidas (9,12) . Rojas-Torres J et al, en su trabajo de investigación sobre actitudes, percepciones y preferencias de individuos de Temuco (Chile) sobre el marcado de prótesis dental, obtienen como resultado que el 90.56% de la población marcaria su prótesis con algún sistema, prefiriendo los códigos QR o tarjeta micro SIM (13) .…”
Section: Marcado Mediante Un Código Qrunclassified
“…Con esta premisa, se ha valorado el marcado de las prótesis dentales, porque puede ofrecer información para el reconocimiento rápido de los individuos, a través de datos como: número de tarjeta de identidad, número de seguro social, número de licencia de conducir, fecha de nacimiento, sexo y otros (7) y mediante el uso de técnicas más complejas como el uso códigos 2D de barras y microchips, que permiten acceder a la historia odontológica y médica del paciente (8) .En la literatura se han encontrado diferentes técnicas de marcado que pueden ser utilizadas por los odontólogos e implementadas por los gobiernos, dependiendo de los beneficios que estas puedan brindar (9) . Se refiere que el marcado de prótesis dentales esta regulado en países como Suecia, Islandia y en 21 estados de Estados Unidos de América (2) .…”
Section: Introductionunclassified
“…The incorporation of the QR code was another aspect that presented different conducts among the studies. In general, itwas reported that the QR code was laminated after being printed and cut, which means that it was wrapped with a layer of laminated paper and then incorporated into the denture by means of a self-curing acrylic resin cover5,6,10,11 . However, Jain et al(2015) 12 presented a new technique using a 1mm thick prefabricated acrylic sheet, which was placed above the already laminated QR code and positioned in the prosthesis, and then the edges of the lamina were fused to the prosthesis by means of self-curing acrylic resin.…”
mentioning
confidence: 99%